2018
DOI: 10.3892/mmr.2018.8947
|View full text |Cite
|
Sign up to set email alerts
|

An active component containing pterodontic acid and pterodondiol isolated from Laggera pterodonta inhibits influenza A virus infection through the TLR7/MyD88/TRAF6/NF‑κB signaling pathway

Abstract: The influenza virus is a pathogen that can cause pandemic and epidemic outbreaks, and therefore represents a severe threat to human health. Antiviral drugs have an important role in the prevention and treatment of influenza, although the increasing emergence of drug resistance has given rise to a requirement for the development of novel antiviral drugs. In the present study, an active component (C8) isolated from Laggera pterodonta was evaluated. The nuclear magnetic resonance spectroscopy and mass spectrometr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 29 publications
0
4
0
Order By: Relevance
“…Others have demonstrated that a pterodontic acid-rich composition from L. pterodonta is effective against a broad spectrum of influenza viruses, including human and avian influenza virus infection (Wang et al, 2018). This mode of action was associated with inhibition of…”
Section: Catalpolmentioning
confidence: 99%
See 1 more Smart Citation
“…Others have demonstrated that a pterodontic acid-rich composition from L. pterodonta is effective against a broad spectrum of influenza viruses, including human and avian influenza virus infection (Wang et al, 2018). This mode of action was associated with inhibition of…”
Section: Catalpolmentioning
confidence: 99%
“…Besides this, the study showed the in vitro antiviral activity of pterodontic acid by inhibition of influenza A virus replication via blocking the nuclear export of viral ribonucleoprotein complexes. Others have demonstrated that a pterodontic acid‐rich composition from L. pterodonta is effective against a broad spectrum of influenza viruses, including human and avian influenza virus infection (Wang et al, 2018). This mode of action was associated with inhibition of TLR7, MyD88, TNF receptor‐associated factor, in addition to dampening the p65 phosphorylation in A549 human alveolar basal epithelial cells.…”
Section: Antiinflammatory Phytochemicals During Viral Infectionmentioning
confidence: 99%
“…Protein concentration was measured using a bicinchoninic acid protein assay kit (Invitrogen Life Technologies). Western blots were performed on PVDF membranes as described, using primary antibodies (CST Biological Reagents) to identify TLR-3, RIG-I, IRF-3, p -IRF-3, p 65, p - p 65, ERK, p -ERK, Akt, p -Akt, p 38, p - p 38, STAT2, p -STAT2, and GAPDH at a dilution following the manufacturer’s protocol. After incubation with primary antibodies, horseradish peroxidase-conjugated secondary antibody (CST Biological Reagents) was added to PVDF membranes for 60 min at room temperature (RT).…”
Section: Materials and Methodsmentioning
confidence: 99%
“…Infection with one serotype generates antibodies that may cross-react and enhance infection with other serotypes in a secondary infection [7]. No specific treatment exists for dengue fever, and vector control has been largely ineffective at preventing the rapid geographic spread of the disease [8][9][10]. Therefore, it is necessary to develop an innovative antiviral drug.…”
Section: Introductionmentioning
confidence: 99%